A study of Cadmium Concentration, Its Transport and Distribution with Distance in the Jhalana Dungari Area, Jaipur - Suruchi Gupta, (Mrs.) (Asian Journal of Chemistry, 2010)
Extensive quarrying activities in the Jhalana Dungari area of Jaipur are going on for over 25 years. Greenokite mineral (CdS) present in the area results in high concentration of Cd in the soil as well as in the water of the area. This paper presents the results of analysis of soil, rock and water samples for determining concentration of Cd, its transport and distribution with distance for the quarrying area. The findings reveal that in water samples the values are between 0.04-0.10 mg/L, which are considerably higher than the prescribed limits of WHO and US standards. Soil samples have Cd in varying concentration ranging from 0.40-1.50 mg/L. It has been found that Cd is distributed throughout the hill, but the concentration is higher around 20 metres from the base.